Preparation of Fe2O3-TiO2 and its Photocatalytic Reduction of CO2 to Methanol - Wang, Jianbo; Liu, Huijuan; Xu, Yanfeng; Zhang, Xiaolong (Asian Journal of Chemistry, 2014)
Fe2O3-TiO2 nanoparticles were synthesized by sol-gel method and characterized by XRD, FTIR and UV-visible. The effect of the calcination temperature, the Fe2O3 composite light for the photocatalytic reduction of CO2 to methanol was studied. Results showed that low recombination of Fe2O3 promote anatase type into rutile type and the high amount of composite inhibited the anatase type into rutile type. When the composite mass fraction of Fe2O3 was 1 %, the catalyst was calcined at 600 °C, catalyst dosage was 2.0 g/L, the flow rate of CO2 was 200 mL/min, and the reaction time was 7 h, the reaction temperature was 90 °C, the reaction solution concentration of NaOH and Na2SO3 were 0.10 mol/L, the yield of methanol was as high as 319.42 μ mol/g. And exploring the mechanism of Fe2O3-TiO2 catalyst photocatalytic reduction of CO2.